2007
DOI: 10.2307/4541118
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Test of the Immunocompetence Handicap Hypothesis in a Teleost Fish: 11-Ketotestosterone Suppresses Innate Immunity in Three-Spined Sticklebacks

Abstract: The immunocompetence handicap hypothesis (ICHH) provides a functional explanation for how sexual ornaments can provide honest signals of male quality. A key aspect of this hypothesis is that testosterone (T) has a bimodal effect: a higher T level enhances the expression of ornaments (increasing mating success and, ultimately, fitness); however, at the same time, it suppresses immune function. Tests of the latter assumption, which have focused mainly on aspects of adaptive immunity in birds, led to equivocal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…In the present study, stream sticklebacks showed extremely high respiratory burst activity during the heat wave. Such high levels of respiratory burst activity are potentially harmful for the host itself, as oxygen radicals might lead to increased oxidative stress and self-tissue damage (Kurtz et al 2006(Kurtz et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, stream sticklebacks showed extremely high respiratory burst activity during the heat wave. Such high levels of respiratory burst activity are potentially harmful for the host itself, as oxygen radicals might lead to increased oxidative stress and self-tissue damage (Kurtz et al 2006(Kurtz et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Folstad & Karter (1992) suggested that increased hormonal levels suppress immune function, and the link to male displays may therefore function as an honest signal of male quality. This link has not been unequivocally demonstrated in fish, but indirect support for this theory exists (Kurtz et al 2007). …”
Section: Reproductive Behaviour Of Farmed and Wild Males And Femalesmentioning
confidence: 99%
“…Several anatomical and morphological changes were observed in lymphoid tissues following exposure to xenoestrogens and xenoandrogens. Spleno-somatic and hepato-somatic indices and thymus volume are affected by exposure to sex-steroids (androgens and estrogens) or to their related endocrine disruptor compounds (Grinwis et al, 2009;Kurtz et al, 2007;Tellez-Banuelos et al, 2009;van Ginneken et al, 2009). In the gilthead seabream the dietary intake of 17 -ethynilestradiol promotes the up-regulation of several genes related with leukocyte recruitment (e.g.…”
Section: Effects Of Endocrine Disruptors On the Immune Responsementioning
confidence: 99%